An in vitro system for the rapid functional characterization of genes involved in carotenoid biosynthesis and accumulation. (8th January 2014) - Bai, Chao; Rivera, Sol M.; Medina, Vicente; Alves, Rui; Vilaprinyo, Ester; Sorribas, Albert; Canela, Ramon; Capell, Teresa; Sandmann, Gerhard; Christou, Paul; Zhu, Changfu
Summary We have developed an assay based on rice embryogenic callus for rapid functional characterization of metabolic genes. We validated the assay using a selection of well‐characterized genes with known functions in the carotenoid biosynthesis pathway, allowing rapid visual screening of callus phenotypes based on tissue color. We then used the system to identify the functions of two uncharacterized genes: a chemically synthesized β–carotene ketolase gene optimized for maize codon usage, and a wild‐type Arabidopsis thaliana ortholog of the cauliflower Orange gene. In contrast to previous reports (Lopez, A.B., Van Eck, J., Conlin, B.J., Paolillo, D.J., O'Neill, J. and Li, L. (2008) J. Exp. Bot. 59, 213–223; Lu, S., Van Eck, J., Zhou, X., Lopez, A.B., O'Halloran, D.M., Cosman, K.M., Conlin, B.J., Paolillo, D.J., Garvin, D.F., Vrebalov, J., Kochian, L.V., Küpper, H., Earle, E.D., Cao, J. and Li, L. (2006) Plant Cell 18, 3594–3605), we found that the wild‐type Orange allele was sufficient to induce chromoplast differentiation. We also found that chromoplast differentiation was induced by increasing the availability of precursors and thus driving flux through the pathway, even in the absence of Orange. Remarkably, we found that diverse endosperm‐specific promoters were highly active in rice callus despite their restricted activity in mature plants. Our callus system provides a unique opportunity to predict the effect of metabolic engineering in complex pathways, and provides a starting point for quantitative modeling and the rational design of engineering strategies using synthetic biology. We discuss the impact of our data on analysis and engineering of the carotenoid biosynthesis pathway.